2007
DOI: 10.1097/fbp.0b013e3281f19c18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the mGluR1 antagonist A-841720 in rat models of pain and cognition

Abstract: In the current study we compared the potency of the selective metabotropic glutamate receptor (mGluR1) antagonist A-841720 (7-Azepan-1-yl-4-dimethylamino-7H-9-thia-1,5,7-triaza-fluoren-8-one) in rodent models of pain with its effects in models of learning and memory, to obtain information regarding the therapeutic window of this compound. A-841720 significantly reduced formalin-induced behaviours and complete Freund's adjuvant (CFA)-induced tactile allodynia, starting at doses of 1 and 10 mg/kg, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…REVIEW without supporting patents, suggests that there may be a mechanistic safety issue with mGlu 1 antagonism. This is supported by independent reports from Johnson and Johnson, 29 Pfizer, 30 Merz, 31 and Abbott 32 related to behavioral side effects and low therapeutic indecies for a range of structurally differentiated mGlu 1 chemotypes. Johnson and Johnson 29 reported that full occupancy of mGlu 1 reeceptors in the cerebellum and thalamus is associated with acquisition and retention impairment in a spatial water maze task.…”
Section: Acs Chemical Neurosciencementioning
confidence: 70%
See 2 more Smart Citations
“…REVIEW without supporting patents, suggests that there may be a mechanistic safety issue with mGlu 1 antagonism. This is supported by independent reports from Johnson and Johnson, 29 Pfizer, 30 Merz, 31 and Abbott 32 related to behavioral side effects and low therapeutic indecies for a range of structurally differentiated mGlu 1 chemotypes. Johnson and Johnson 29 reported that full occupancy of mGlu 1 reeceptors in the cerebellum and thalamus is associated with acquisition and retention impairment in a spatial water maze task.…”
Section: Acs Chemical Neurosciencementioning
confidence: 70%
“…Merz and Abbott both profiled A-841720 in pain efficacy models while also assessing motor and cognitive function side effects. 31,32 A-841720 worked at doses beginning at 1 mg/kg in the CFA pain model, going on to give full efficacy at 10 mg/kg. However, significant motor side effects were seen at these analgesic doses with the compound causing impaired cognitive function in water maze tests.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%
See 1 more Smart Citation
“…A classical 8-radial arm maze for mice (More et al, 2008;More et al, 2007) was placed on the water tank with 4 out 8 arms kept open to form a cross. Each mouse was singly released in the centre of the maze and tracked for 10 minutes with AnyMaze4.99 tracking software.…”
Section: Spontaneous Alternation Test For Spatial Working Memorymentioning
confidence: 99%
“…-N-methyl-N-[4-[6-(propan-2ylamino)pyrimidin-4-yl]-1,3-thiazol-2Union of Pure and Applied Chemistry; MoA, mechanism of action; pK B , negative logarithm of the equilbrium dissociation constant for an allosteric ligand; pEC 50 , negative logarithm of the agonist or PAM concentration required to give the half-maximal response (activation or potentiation); pIC 50 , negative logarithm of the NAM concentration required to give the half-maximal inhibition.a Where affinity estimates were unavailable pIC 50 (NAMs) or pEC 50 (PAMs) values are reported indicated by italics. b 1)Zheng et al, 2005;El-Kouhen et al, 2006;Morè et al, 2007;Zhu et al, 2008. 2) Carroll et al, 2001De Vry et al, 2001;Lavreysen et al, 2003;Schröder et al, 2008;Cho et al, 2014a.…”
mentioning
confidence: 99%